Analisis Penerapan Budaya Sekolah dalam Pembentukan Karakter Siswa di Sekolah MAN 2 Model Medan - Suhendra Suhendra; Sayyidina Sayyidina; Sumila Sumila; Pitri Aulia Usman Lubis; Andi Taufiq Umar (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research aims to explore and analyze how school culture is applied in forming the character of MAN 2 Model Medan students. The method used for this research uses descriptive qualitative research methods which also include interview-based field data. This research is descriptive in nature and seeks to examine and report the actual conditions at the research location. It is not experimental in nature because it does not try to test a particular hypothesis but only explains “what is” about a variable, symptom or condition being studied. The data used in this research is secondary and primary, obtained from books, journals, articles and other sources relevant to the application of school culture in character building for MAN 2 Model Medan students. Data collection techniques use various data collection methods, including interviews, observation, documentation and collecting reading material related to the problems studied. The results of this research indicate that the strategy of implementing culture in schools is considered effective in forming student characters that are in accordance with school culture. Teachers use persuasive communication which consists of providing material, warnings and consultations to help students develop character that is in accordance with school culture. The results of this research also show that developing a school culture that promotes religious and social values is very important in forming good student character.